The "Developing Numerical Literacy Through Problem-Based Learning Model Using Mathematics Card Media (KARMAT)": "Developing Numerical Literacy Through Problem-Based Learning Model Using Mathematics Card Media (KARMAT)" - Setiadi, Fibianse (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of students' ability to write numbers is caused by a teaching method in mathematics that does not encourage serious reading and skill application. This study aims to improve students' numerical literacy through the problem-based learning (PBL) model. The subjects are 18 fifth-grade students from SD Negeri Sarirejo Semarang for the 2023/2024 academic year, using observation sheets and number writing skill tests as tools. The results indicate that the implementation of PBL increased the average numerical skill score from 75% in cycle I to 90% in cycle II, as well as enhancing students' interest and motivation in learning.